Intention to Use Islamic Mobile Banking: Integration of Technology Acceptance Model and Theory of Planned Behavior with Trust - Joko Setyono (IAIN Salatiga, 2022)
This study intended to examine the variables influencing the interest in mobile banking at three Islamic banks in Yogyakarta, namely BSI, Mualamat, and BCA Syariah. The quantitative method was employed, alongside the integration of the TAM and TPB approaches with trust. Sampling was conducted using the purposive method, with questionnaires as the data collection technique. A total of 118 Yogyakarta Islamic mobile banking customers and users constituted the respondents. The data were analyzed with Warp PLS 6.0 analysis tool using the Multivariate SEM-PLS method. Subsequently, the SEM-PLS analysis results showed a high level of interest in Islamic mobile banking by customers. Islamic mobile banking simplifies financial transactions and boosts efficiency and productivity. The results of this study are anticipated to increase the standard of mobile banking services and customer service.